Multiple Phenotypic Changes Define Neutrophil Priming - Miralda, Irina; Uriarte, Silvia M.; McLeish, Kenneth R. (Frontiers in Cellular and Infection Microbiology, 2017)
Exposure to pro-inflammatory cytokines, chemokines, mitochondrial contents, and bacterial and viral products induces neutrophils to transition from a basal state into a primed one, which is currently defined as an enhanced response to activating stimuli. Although, typically associated with enhanced generation of reactive oxygen species (ROS) by the NADPH oxidase, primed neutrophils show enhanced responsiveness of exocytosis, NET formation, and chemotaxis. Phenotypic changes associated with priming also include activation of a subset of functions, including adhesion, transcription, metabolism, and rate of apoptosis. This review summarizes the breadth of phenotypic changes associated with priming and reviews current knowledge of the molecular mechanisms behind those changes. We conclude that the current definition of priming is too restrictive. Priming represents a combination of enhanced responsiveness and activated functions that regulate both adaptive and innate immune responses.